2019
DOI: 10.1111/jocn.14868
|View full text |Cite
|
Sign up to set email alerts
|

Influencing factors when living with Parkinson’s disease: A cross‐sectional study

Abstract: Aims and objectives: To identify the personal-and disease-related factors that are associated with living with Parkinson's disease. Background: Living with Parkinson's disease affects the physical, psychological, social and spiritual areas of the person. Health professionals need to know which factors influence the daily living with Parkinson's disease, in order to facilitate a positive living. Design: A multicentre cross-sectional study. Methods: A total of 324 patients with Parkinson's disease diagnoses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 36 publications
6
34
0
Order By: Relevance
“…On the other hand, many patients believe their healthcare is not su ciently individualised [49]. Prior analyses of patients with Parkinson's disease have shown that social support, followed by satisfaction with life and by socioeconomic status, are the only factors relevant to the patient's coexistence with the disease [50]. If these factors were equally in uential with respect to T2DM, we would be facing a scenario in which social factors exerted signi cant in uence on health conditions and should be taken into account when socio-health policies are designed and applied.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, many patients believe their healthcare is not su ciently individualised [49]. Prior analyses of patients with Parkinson's disease have shown that social support, followed by satisfaction with life and by socioeconomic status, are the only factors relevant to the patient's coexistence with the disease [50]. If these factors were equally in uential with respect to T2DM, we would be facing a scenario in which social factors exerted signi cant in uence on health conditions and should be taken into account when socio-health policies are designed and applied.…”
Section: Discussionmentioning
confidence: 99%
“…It is a complex and disabling disorder manifested through a combination of motor and non-motor symptoms that generate an important impact on the daily living [ 2 ]. Throughout the PD course, patients do not only experience a progressive intensification of symptoms, but also have to deal and cope with an increasing limitation in all areas of their day to day, as a consequence of the disease [ 3 , 4 ]. Several studies show that living with PD affects the patients’ physical state together with other essential aspects in their lives, such as the psychological, social and spiritual ones [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, many patients believe their healthcare is not su ciently individualised [47]. Prior analyses of patients with Parkinson's disease have shown that social support, followed by satisfaction with life and by socioeconomic status, are the only factors relevant to the patient's coexistence with the disease [48]. If these factors were equally in uential with respect to T2DM, we would be facing a scenario in which social factors exerted signi cant in uence on health conditions and should be taken into account when socio-health policies are designed and applied.…”
Section: Discussionmentioning
confidence: 99%